Rabbit : husbandry, health and production - Lebas, F. (FAO RomeIT, 1986)
Reviews world production and trade of rabbit meat and skins. Describes anatomy and physiology of rabbit, its feeding behaviour, nutritional needs and the types of feed suited to its production. Examines rabbit production noting the reproductive rates and the appropriate environment. Explains genetics of rabbit breeds and of breeding characters and outlines selection methods and crossbreeding strategies that foster genetic improvement. Discusses diagnosis and treatment of rabbit diseases, housing and equipment, rabbitry management, production of rabbit skins and wool, and the link between rabbit breeding and rural development.